Hämophilie-Zentrum Bonn 1980 – 2009 - Besmens, I.; Brackmann, H.-H.; Oldenburg, J. (Hämostaseologie, 2011)
The Bonn Haemophilia Care Center provides patient care on a superregional level. The centre’s large service area is, in part, due to the introduction of haemophilia home treatment and related to this the individualized prophylaxis in children and adults by Egli and Brack-mann in Bonn in the early 1970s, that represented a milestone in German haemophilia therapy. Epidemiologic patient data from the two selected time points, 1980 and 2009, are evaluated to illustrate the change in the composition of the patient clientele. In 1980 a total of 639 patients were treated at the Bonn Haemophilia Center. 529 patients exhibited a severe form and 110 a non-severe form of the respective clotting disorder. In 2009 the Bonn Haemophilia Center took care for a total of 837 patients. There were 445 patients who suffered from a severe form of the considered clotting disorder while 392 showed a non-severe course. The number of less severely affected patients has increased significantly in 2009. Patients in 1980 were predominantly suffering from a severe form and most had to travel more than 150 km from their homes to the treatment center. In 2009 the number of patients living a medium-long distance from the care provider has significantly increased while the number of patients living more than 150km from the center has decreased. Comparing 2009 to 1980 a growth of the center’s regional character becomes apparent, especially when patient age and severity of the coagulation disorder are taken into consideration. The regional character was more strongly pronounced with milder disease severity and lower patient age. Due to the existence of well established primary haemophilia care in CCCs in Germany, the trend for the recent years is that the proportion of young patients that choose haemophilia care providers closer to their homes is increasing.
Keywords: Haemophilia; haemophilia A; haemophilia B; von Willebrand disease; epidemiology; factor VIII; factor IX; Haemophilia Center Bonn; catchment area; home treatment